THE EFFECTIVENESS OF ONLINE LEARNING PLATFORMS IN TEACHING ENGLISH AS A FOREIGN LANGUAGE (Ustozlar uchun, 2026)
Online learning platforms have become an important part of English as a Foreign Language instruction. This thesis examines how such platforms support language learning, what benefits are commonly reported, and what limits reduce their effectiveness. The topic is analyzed through a descriptive and comparative review of recent studies on EFL online learning, student engagement, digital readiness, and synchronous and asynchronous teaching. The reviewed studies show that online platforms can support vocabulary work, grammar practice, reading, writing, speaking, and listening when clear tasks, teacher guidance, and regular feedback are provided. At the same time, unstable internet access, weak learner motivation, limited interaction, and low digital readiness can reduce learning results. The thesis concludes that online learning platforms are effective not by themselves, but through purposeful use in a well-planned teaching process.